Differential habitat selection of black bears, gray wolves, and boreal caribou in the Boreal Shield of Saskatchewan - Tomchuk, Patricia 1992- (2019)
Boreal woodland caribou (Rangifer tarandus caribou) are listed as Threatened on Schedule 1 of the Canada Species at Risk Act, and critical habitat for this species is currently being defined across the country. Declines in populations have been driven largely by anthropogenic disturbance, and in this context much research has been directed at caribou habitat selection and that of their predators, including wolves (Canis lupus) and black bears (Ursus americanus). However, in the Boreal Shield of Saskatchewan caribou occur in relatively pristine habitat with low levels of anthropogenic disturbance, a naturally high fire-return interval, and few invasive species. The objectives of my study were to: (i) provide novel information on black bear and wolf ecology in the Boreal Shield of Saskatchewan; (ii) provide a baseline of data from a northern caribou range to which bear-wolf-caribou habitat selection patterns obtained from areas of greater anthropogenic disturbance can be compared; and (iii) examine how the species overlap in habitat selection patterns during the critical calving and post-calving seasons and relate that to potential for predation by black bears relative to wolves. My study was the first of its kind in northern Saskatchewan. Using satellite radio-tracked black bears, wolves, and caribou, I determined that bear habitat selection was strongly phenological, with animals generally selecting for mixed coniferous-deciduous stands in the first half of the active season but transitioning towards selecting younger (berry-producing) coniferous stands, especially jack pine forests, later in the summer and into fall. Bears also showed selection for linear features like roads and trails, and lower elevations (which included drainages). Wolves consistently avoided mature black spruce, a potential caribou refuge, but strongly selected open muskeg habitats, potential habitats for multiple prey species including caribou and moose. Wolves also selected lower elevations but unlike bears they showed an avoidance of ...